Application of Argon Plasma Coagulation for Gastrointestinal Angiodysplasia in Children— Experience From a Tertiary Center - Yeh, Pai-Jui; Le, Puo-Hsien; Chen, Chien-Chang; Chao, Hsun-Chin; Lai, Ming-Wei (Frontiers in Pediatrics, 2022)
Background Argon plasma coagulation (APC) has been applied in adults to treat various diseases, including vascular lesions in the gastrointestinal (GI) tract. However, angiodysplasia (AD) is an uncommon cause of pediatric GI bleeding, while the experience of treating AD with APC was rarely reported. Method Five children with AD in the GI tract successfully treated with APC were reviewed. Results Three of the five patients were girls, and the age at diagnosis ranged from 1.5 months to 10.5 years of age. One patient with gastric AD manifested with tarry stool, and the rest had colonic AD, which caused various degrees of bloody stool. Three patients had evident anemia. All patients received an endoscopic diagnosis, and two had compatible findings in radiographic exams. Each patient underwent one APC treatment session, and none encountered procedure-related complications or re-bleeding. Conclusions AD can be an etiology of GI bleeding even in neonates. APC is an effective and safe therapy for symptomatic AD in children.